Factors Shaping Student Readiness for Online Learning: Technology, Perception, and Lecturer Roles - Diputra, Yudhi; Husin, Muhammad; Fadhilah; Karimi, Amir; Abubakar Yunusa, Abdullahi; Muthma’innah, M (Journal of Education Culture and Society, 2025)
Aim. This study explores factors shaping student readiness for online learning, focusing on learner control, technology readiness, perception of online learning, and lecturer readiness. Methods. The research employs Structural Equation Modeling (SEM) to analyse data collected from 573 electronics students at a university in Indonesia. SEM analysis examined the relationships between these dimensions and their impact on student readiness for online learning. Results and Conclusion. The findings indicate that lecturer readiness significantly enhances student readiness, with technology readiness and perception of online learning also playing crucial roles. While learner control does not directly affect student readiness, it influences readiness by impacting perceptions of online learning. These results emphasise the importance of student autonomy and lecturer support in fostering motivation and engagement in online learning. Research Restrictions. The study is limited to a single study programme and employs a quantitative approach, indicating a need for broader exploration in future research. Practical Application. The findings suggest that educational institutions should invest in professional development for lecturers and technological access for students to optimise the online learning environment. Cognitive Value. This study provides empirical insights into the interconnected factors affecting student readiness for online learning, highlighting the pivotal role of lecturer support and technology in shaping student success.